Domaine : Domaine de Kerguehennec 1994. - Bakirtzis, Charalambos; Hadjimichalis, George; Kirkeby, Per; Rilke, Rainer Maria; Schnapp, Alain; Tiberghien, Gilles A.; Zacharopoulos, Denys (Locminé : Domaine de Kerguehennec, Centre d'Art Locminé, 1995)
Domaine de Kerguehennec, Centre d'Art ; Hajdu, Etienne ; Pan, Marta ; Long, Richard ; West, Franz ; Raynaud, Jean Pierre ; Morellet, François ; Zorio, Gilberto ; Rückriem, Ulrich ; Grand, Toni ; Penone, Giuseppe ; Visser, Carel ; Raetz, Markus ; Bouillon, François ; Sonnier, Keith ; Finlay, Ian Hamilton ; Ballet, Elisabeth ; Totsikas, Thanassis ; Baumann, Thomas ; Nordman, Maria ; Steir, Pat ; Neuhaus, Max ; Smithson, Robert ; Heizer, Michael ; Mullican, Matt ; Kirkeby, Per ; Hadjimichalis, George ; Absalon ; Leroy, Eugène ; Federle, Helmut ; Brandl, Herbert ; Richter, Gerhard ; Toroni, Niele ; Spalletti, Ettore ; Simoni, Mariella ; Lutes, Jim ; Dorner, Helmut ; Gerber, Gaylen ; Noiret-Thomé, Xavier ; Schiess, Adrian ; Calzolari, Pierpaolo ; Carroll, Lawrence ; Walravens, Daniel ; Collin-Thiébaut, Gérard ; Gherban, Alexandre
Engels
Frans
boek